Practice of integrated vector surveillance of arthropod vectors, pathogens and reservoir hosts to monitor the occurrence of tropical vector-borne diseases in 2020 in Zhejiang Province, China - Wu, Yuyan; Wang, Jinna; Liu, Qinmei; Li, Tianqi; Luo, Mingyu; Gong, Zhenyu (Frontiers in Veterinary Science, 2022)
Background Vector-borne diseases have become one of the most serious local public health threats. Monitoring and controlling vectors are important means of controlling vector-borne diseases. However, traditional vector surveillance systems in China mainly monitor vector density, making its early-warning effect on vector-borne diseases weak. In this study, we applied an integrated surveillance system of multiple arthropod vectors and reservoir host containing ecology, etiology, and drug resistance monitoring to obtain better knowledge on vector populations and provide early warning of suspicious vector-borne infectious disease occurrence. Methods An ecology surveillance of mosquitoes, rodents, ticks, and chigger mites, a pathogen infection survey on mosquitoes and rodents, and a drug resistance survey on Aedes albopictus were conducted in 12 cities in Zhejiang Province in 2020. Results A total of 15,645 adult mosquitoes were collected at a density of 19.8 mosquitoes per Centers for Disease Control and Prevention light trap. Culex tritaeniorhynchus (72.76%) was the most abundant species. The Breteau index of Ae. albopictus was 13.11. The rodent density was 0.91 rodents per hundred traps; the most abundant species was Rattus norvegicus (33.73%). The densities of dissociate and ectoparasitic ticks were 0.79 ticks per hundred meters and 0.97 ticks per animal, respectively. The most abundant tick species was Haemaphysalis longicornis (56.38%). The density of chigger mites was 14.11 per rodent; two species were identified, with the most abundant species being Walchia spp. mite (68.35%). No flavivirus or alphavirus was found in mosquito etiology monitoring, whereas the positivity rates of hantavirus, the pathogenic bacteria Leptospira spp., Orientia tsutsugamushi, and Bartonella spp. detected in rodent etiology monitoring were 1.86, 7.36, 0.35 and 7.05%, respectively. Field populations of Ae. albopictus in Zhejiang Province were widely resistant to pyrethroids but sensitive to most insecticides tested, including organophosphorus and carbamate insecticides. Conclusion Integrated surveillance systems on multiple arthropod vectors (mosquitoes, ticks, mites) and animal reservoirs (rodents) can provide important information for the prevention and control of epidemic emergencies.